The acute effects of physiotherapy on general movement patterns in preterm infants: A single-blind study - Kepenek-Varol, Busra; Tanriverdi, MÜBERRA; TANRIVERDİ, MÜBERRA; Iscan, AKIN; İŞCAN, AKIN; Alemdaroglu-Gurbuz, Ipek (My University, 2019)
Background: The General Movement Assessment (GMA) is a video analysis method developed by Heinz Prechtl that examines the infant-s spontaneous movements. In recent years, although many studies have been performed in preterm infants by applying GMA, few studies have shown the effects of early intervention on GMA.